Influences of the technological parameters on the surface twist in grinding - Nagy, Nora; Kundrak, Janos (НТУ "ХПИ", 2016)
The requirement towards to the functional surfaces of the machine components became higher over the time. The final steps in the machining are supposed to create a surface which ensures wear resistance, longer lifetime and has special features on demand as well. The twist free surface can be considered as a special surface condition. The following paper presents the effect of the grinding parameters to the surface twist.

Требования в отношении функциональных поверхностей деталей машин повысились с течением времени. Предполагается, что на окончательных этапах механической обработки должна создаваться поверхность, которая обеспечивает износостойкость, длительный срок службы, а также обладает специальными требуемыми характеристиками. Закручивание свободной поверхности может рассматриваться как особое состояние поверхности. В представленной статье исследуется влияние режимов шлифования на закручивание поверхности.
Keywords: surface roughness; grinding parameters; well-defined geometry; sealing surfaces; закручивание поверхности; шероховатость; режимы шлифования